PENGARUH VARIABEL MAKROEKONOMI DAN VOLATILITAS SAHAM–SAHAM DI JAKARTA ISLAMIC INDEX ( JII ) TERHADAP INVESTASI EFEK PERUSAHAAN ASURANSI SYARIAH DI INDONESIA - Rika Christina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
Investment is an investment activity or keep a number of assets in the hope of future capital or assets can increase in value as well as to maintain the integrity of the capital or assets owned by the investor. This study aims to determine whether the volatility of stocks listed in the Jakarta Islamic Index (JII) and macroeconomic variables that include: GDP, inflation, BI rate, and the exchange rate of US influential on investment securities Islamic insurance company in Indonesia.Population and sample in this research are monthly time series data starting in April 2013-December 2015 were obtained from the database of the Otoritas Jasa Keunagan (OJK), the Badan Pusat Statistik (BPS), Bank Indonesia, and Yahoo finance. The sampling method used is purposive sampling. The analytical method used is multiple regression analysis. The results showed individually variable volatility in Jakarta Islamic Index no significant effect on investment securities Islamic insurance company in Indonesia. GDP and inflation significant negative effect on investment securities Islamic insurance company in Indonesia. BI rate and the exchange rate of US no significant effect on investment securities Islamic insurance company in Indonesia.Keywords: investment securities, volatility, macroeconomics variables